Polypharmacy and bone fracture risk in patients with type 2 diabetes: The Fukuoka Diabetes Registry. (November 2021) - Komorita, Yuji; Ohkuma, Toshiaki; Iwase, Masanori; Fujii, Hiroki; Oku, Yutaro; Higashi, Taiki; Oshiro, Ayaka; Sakamoto, Wakako; Yoshinari, Masahito; Nakamura, Udai; Kitazono, Takanari
Highlights: The association between polypharmacy and bone fracture risk is unknown in diabetics. Number of prescribed drugs was associated with higher bone fracture risk in type 2 diabetes. The association remained significant after adjustment for fracture risk factors. Drug reviews and polypharmacy management are important in diabetic patients at higher risk of fractures. Patients with polypharmacy should take fracture-prevention measures in their daily life. Abstract: Aims: To prospectively investigate the association between the number of prescribed drugs and the fracture risk in patients with type 2 diabetes. Methods: Japanese participants with type 2 diabetes (n = 4, 706; 2, 755 men, 1, 951 postmenopausal women; mean age, 66 years) were followed for a median of 5.3 years and grouped on the basis of the number of prescribed drugs at baseline. The main outcomes were fractures at any anatomic site and fragility fractures (fractures at hip and spine sites). Results: During follow-up, any fracture occurred in 662 participants. The overall age- and sex-adjusted fracture incidence rates per 1, 000 person-years were 21.2 (0–2 drugs), 28.1 (3–5 drugs), 37.7 (6–8 drugs), and 44.0 (≥9 drugs) ( p for trend < 0.001). Compared with 0–2 drugs, the multivariate-adjusted hazard ratios (HRs) (95% confidence intervals [CIs]) for fractures were 1.34 (1.07–1.68) for 3–5 drugs, 1.76 (1.37–2.26) for 6–8 drugs, and 1.71 (1.27–2.31) in ≥ 9 drugs. The multivariate-adjusted HR (95% CI) per increment in drugs was 1.05 (1.02–1.08) (p < 0.001). Similar tendencies were observed for fragility fractures. Conclusions: A greater number of prescribed drugs is associated with an increased bone fracture risk in patients with type 2 diabetes.